Zooplankton - Richardson, AJ; McKinnon, D; Kerrie Swadling (2009)
Currently, there are no published observed impacts of climate change on zooplankton in Australian waters; rather than evidence of a lack of response, this dearth of knowledge is probably due to the lack of long-term datasets on Australian zooplankton. Anecdotally, there is evidence that some subtropical species are extending their range southwards (polewards) along the east coast of Tasmania as a result of the southwards penetration of the East Australian Current, while typically cold-water species are retracting towards the pole. The three most important aspects of climate change for zooplankton are temperature, acidification and nutrient enrichment, based on knowledge of impacts of climate change on zooplankton from research around the world. In the northern hemisphere, zooplankton distributions are moving north (polewards) as the seas warm, leading to new re-arrangement of plankton communities. The timing of zooplankton peak abundance appears to be responding faster than the timing of biological events of terrestrial animals and plants such as breeding and blossoming. However, in temperate regions, the timing of peaks in abundance of various plankton functional groups does not always respond to ocean warming synchronously, resulting in a mismatch between predators and the availability of their prey. Ocean acidification may mean that calcifying zooplankton such as pteropods, decline first in the Southern Ocean and later from mainland Australian waters. Indirect impacts of climate change on the nutrient enrichment regime could outweigh the direct impacts of temperature change and ocean acidification, particularly in oligotrophic (low nutrient) tropical regions with little seasonality, such as those in Northern Australia. Changes to the zooplankton community in response to changes in temperature, acidification and in particular nutrient enrichment will resonate throughout